Relation between structure and piezoelectric properties of (1-x-y)PbZrO3-xPbTiO(3)-yPb(Ni1/3Nb2/3)O-3 ceramics near triple point composition - Lee, Tae-Gon; Lee, Ho-Jun; Kim, Dae-Hyeon; Xu, HaiBo; Park, Su-jin; Park, Jong-Seong; Nahm, Sahn; Kang, Chong-Yun; Yoon, Seok-Jin (ELSEVIER SCI LTD, 2016)
The structural and piezoelectric properties of (1-x-y)PbZrO3-xPbTiO(3)-yPb(Ni1/3Nb2/3)O-3 [(1-x-y)PZ-xPT-yPNN] ceramics near the triple point were investigated. The 0.16PZ-0.34PT-0.5PNN ceramic with a triple point composition exhibited a large d(33), k(p) and epsilon(T)(33)/epsilon(o) values of 855 pC/N, 0.68 and 5800, respectively. However, its g(33) and d(33) x g(33) values were relatively small because of its large epsilon(T)(33)/epsilon(o). Similar results were obtained for specimens with rhombohedral-tetragonal or pseudocubic-tetragonal morphotropic phase boundary (MPB) compositions. However, specimens with a rhombohedral structure near the rhombohedral-tetragonal MPB exhibited large g(33) and d(33) x g(33) values because of their large d(33) and small epsilon(T)(33)/epsilon(o) that can be explained by their polarization characteristics. In particular, 0.23PZ-0.36PT-0.41PNN ceramic exhibited large g(33) and d(33) x g(33) values of 30.2 x 10(-3) Vm/N and 22.6 x 10(-12) m(2)/N, respectively, thus making it a good candidate for piezoelectric energy harvesters and multilayer actuators. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: MORPHOTROPIC PHASE-BOUNDARY; MULTILAYER ACTUATORS; SYMMETRY; STRAIN